Aggregation and other biases in the calculation of consumer elasticities for models of arbitrary rank - Frank T. Denton; Dean C. Mountain (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2011)
Consumer-related policy decisions often require analysis of aggregate responses or mean elasticities. However, in practice these mean elasticities are seldom used. Mean elasticities can be approximated using aggregate data, but that introduces aggregation bias for full and compensated price elasticities, though interestingly not for expenditure elasticities. The biases corresponding to incorrect approximations of mean elasticities depend on the type of data (micro or aggregate), the type and rank of the model, and generalized measures of income inequality. These biases are distinct from the biases (already noted in the literature) when using aggregate data to estimate micro elasticites at mean income.
Keywords: D11; C43; 330; aggregate price and expenditure elasticities; aggregation bias; consumer demand; generalized measures of income inequality; income distribution; Gesamtwirtschaftlicher Konsum; Nachfrage; Einkommensverteilung; Soziale Ungleichheit; Preiselastizität; Einkommenselastizität; Theorie